Java project on periodontal diseases: a study on transmission of Porphyromonas gingivalisin a remote Indonesian population - A. J. van Winkelhoff (Blackwell Synergy, 2007)
Aim: To study transmission of Porphyromonas gingivalis in a population living in a remote area in Southern Java, Indonesia. Material and Methods: Subgingival plaque samples from 167 subjects with varying degrees of periodontal breakdown were obtained and cultured for the presence of P. gingivalis. After extraction and purification of bacterial DNA, amplified fragment length polymorphism technique was applied to genotype the bacterial isolates. Computer-assisted analysis of the bacterial DNA profiles was used to study distribution of P. gingivalis genotypes within family units. Results: One hundred and five of the 167 (63%) subjects were culture positive for P. gingivalis. In total, 371 P. gingivalis isolates were obtained from the 105 subjects. Of the 105 subjects, 30 were siblings representing 13 families. In six of the 13 families (46%), identical P. gingivalis genotypes were found among siblings. In the study group of 105 subjects, 13 married couples were identified of which both spouses were culture positive for P. gingivalis. None of the 13 couples shared an identical P. gingivalis genotype. Twenty P. gingivalis-positive subjects had spouses that were culture negative for P. gingivalis. Conclusions: In this study population, vertical transmission of P. gingivalis has occurred within family units, most likely from parents to children. Transmission of P. gingivalis between spouses could not be established.